INVESTIGATION OF URINARY EXCRETION OF HYDROXYETHYL STARCH AND DEXTRAN BY UHPLC-HRMS IN DIFFERENT ACQUISITION MODES - Esposito, S.; Deventer, K.; Giron, A.J.; Roels, K.; Herregods, L.; Verstraete, A.; Van Eenoo, P. (Biology of Sport, 2014)
Plasma volume expanders (PVEs) such as hydroxyethyl starch (HES) and dextran are misused in sports because they can prevent dehydration and reduce haematocrit values to mask erythropoietin abuse. Endogenous hydrolysis generates multiple HES and dextran oligosaccharides which are excreted in urine. Composition of the urinary metabolic profiles of PVEs varies depending on post-administration time and can have an impact on their detectability. In this work, different mass spectrometry data acquisition modes (full scan with and without in-source collision-induced dissociation) were used to study urinary excretion profiles of HES and dextran, particularly by investigating time-dependent detectability of HES and dextran urinary oligosaccharide metabolites in post-administration samples. In-source fragmentation yielded the best results in terms of limit of detection (LOD) and detection times, whereas detection of HES and dextran metabolites in full scan mode with no in-source fragmentation is related to recent administration (< 24 hours). Urinary excretion studies showed detection windows for HES and dextran respectively of 72 and 48 hours after administration. Dextran concentrations were above the previously proposed threshold of 500 μg · mL-1 for 12 hours. A “dilute-and-shoot” method for the detection of HES and dextran in human urine by ultra-high-pressure liquid chromatography-electrospray ionization-high resolution Orbitrap™ mass spectrometry was developed for this study. Validation of the method showed an LOD in the range of 10-500 μg · mL-1 for the most significant HES and dextran metabolites in the different modes. The method allows retrospective data analysis and can be implemented in existing high-resolution mass spectrometry-based doping control screening analysis.